Svalbox-DOM_2020-0002_Janusfjellet - Betlem, Peter (Zenodo, 2021)
Model description Folding and faulting at Janusfjellet affecting several sandstone (including through the Festningen sandstone) and shale units. Compressive setting with fault-propagation folds. Metadata The included processing report specifies processing parameters that were used as input for the processing software (Agisoft Metashape, v1.6.3.10732). Exported model data use CRS epsg:32633. Svalbox.no Through Svalbox we aim to take geoscientific research and education to the next level – with the simple motto of placing all key information and data sets in their correct spatial position. We bring modern technology, in particular cost-effective virtual outcrops, to complement more than 200 years of geoscientific research on Svalbard. Finally, Svalbox provides a sustainable platform for sharing results, workflows and teaching material with the wider geoscientific community. For more information, contact the Svalbox team at svalbox[at]gmail.com.